Gambaran Pengetahuan Ibu Nifas Tentang Manfaat Senam Nifas di Klinik Katarina Simanjuntak Dusun IV A Sei Mencirim Tahun 2022. - Isabella kristiani Sihaloho; Ermawaty Arisandi; Hetty Gustina Simamora (Universitas Prima Indonesia, 2022)
The puerperium is an important period that must be considered, because at this time the reproductive organs need to return to their normal form and one way is to do puerperal gymnastics. these parts to a normal shape,Help normalize the joints that become loose due to pregnancy and childbirth. The purpose of this study was to determine the description of postpartum mother's knowledge about the benefits of postpartum gymnastics at the Katarina Simanjuntak Clinic, Dusun IV A Sei Mencharming Deli Serdang in 2022. This study used a descriptive method. The sample in this study were postpartum mothers 0-42 days who gave birth or who visited the postpartum clinic Katarina Simanjuntak Hamlet IV A Sei Characterizing the Year 2022 with a total of 30; respondents. Researchers used primary data and secondary data, the questionnaire used in the form of Multiple Choice data was processed using SPSS and presented in the form of an open table. The results of the study are as follows: of the 30 respondents the most knowledgeable with good categories, namely 23 people (76.7%), with sufficient knowledge as many as 7 people (23.3%). The good knowledge of postpartum mothers is due to experience and existing programs in the clinic so that mothers follow the program well, and for mothers: postpartum mothers who have sufficient knowledge and are less expected to be more active in participating in existing programs